2010
DOI: 10.1108/09654281011052646
|View full text |Cite
|
Sign up to set email alerts
|

Professional assistance in implementing school health policies

Abstract: Purpose-The purpose of this study was to evaluate the role of a school health promotion (SHP) advisor in the implementation of the six steps of the Dutch 'Schoolbeat' approach, aimed at establishing health promotion policies and activities in secondary schools. Design-Eighty school board members and 18 prevention coordinators of 18 schools in the Southern Limburg region in the Netherlands completed a written questionnaire on the implementation of the six steps of the Schoolbeat approach, and on their satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 15 publications
(11 reference statements)
6
26
0
Order By: Relevance
“…This was especially evident in the practices relating to the development of a school team and integration of health into school improvement priorities; such practices are cited as being essential in HPS development (International Union of Health Promotion and Education, 2009) but may be more difficult to implement as they require changes in the traditional actions of a school. Boot et al (2010) reported similar findings, in that practical issues are more likely to fit into the daily task of teachers, whereas developing policies and changing school processes were more challenging. This context is particularly relevant to program planners and evaluators involved with HPS as changing these higher level processes requires someone with time, the professional skills and knowledge to develop and implement structural health promotion programs and policies (Boot et al, 2010).…”
Section: Lessons Learnedsupporting
confidence: 76%
See 3 more Smart Citations
“…This was especially evident in the practices relating to the development of a school team and integration of health into school improvement priorities; such practices are cited as being essential in HPS development (International Union of Health Promotion and Education, 2009) but may be more difficult to implement as they require changes in the traditional actions of a school. Boot et al (2010) reported similar findings, in that practical issues are more likely to fit into the daily task of teachers, whereas developing policies and changing school processes were more challenging. This context is particularly relevant to program planners and evaluators involved with HPS as changing these higher level processes requires someone with time, the professional skills and knowledge to develop and implement structural health promotion programs and policies (Boot et al, 2010).…”
Section: Lessons Learnedsupporting
confidence: 76%
“…Boot et al (2010) reported similar findings, in that practical issues are more likely to fit into the daily task of teachers, whereas developing policies and changing school processes were more challenging. This context is particularly relevant to program planners and evaluators involved with HPS as changing these higher level processes requires someone with time, the professional skills and knowledge to develop and implement structural health promotion programs and policies (Boot et al, 2010).…”
Section: Lessons Learnedsupporting
confidence: 76%
See 2 more Smart Citations
“…Clearly defi ned roles between the participants, the institutional infrastructure and anchoring are also vital (Center for Mental Health and Schools 2008 ; Deschesnes et al 2010 ). Systematic approaches to building trust, is another key principle to stimulate partnership development (Boot et al 2010 ).…”
Section: Partnerships and Networkingmentioning
confidence: 99%